Sport and Development in Emerging Nations : International and regional dynamics of sport mega-events - Mahfoud Amara (7236599) (2021)
Since winning the bid to host the 2022 FIFA World Cup, Qatar has been under the spotlight, responding to criticism regarding the working conditions of workers involved in the construction of football stadia and other regulations related to the Kafala system – a system of sponsorship that binds workers to their employers. In response to these criticisms, a number of labour reforms have been implemented, including increasing the minimum wage and lifting the requirement for workers to get permission from their employers to change jobs or exit the country. The other strategy in sport has been to invest more in the sport (football) for development agenda, internally and externally. Internally, the goal is to develop sport projects targeting workers, improve their health and well-being and offer them opportunities to celebrate their diverse cultures. Externally, the strategy is to position Qatar in the international network of sport for development through collaborations with different NGOs, international sport clubs and brands and sport personalities to act as ambassadors of these different projects. The chapter focuses on football for development in Qatar led by Generation Amazing, a branch of the Supreme Committee (SC) for the Delivery and Legacy of the 2022 FIFA World Cup. Other Information Published in: Sport and Development in Emerging Nations License: https://creativecommons.org/licenses/by-nc-nd/4.0/ See chapter on publisher's website: http://dx.doi.org/10.4324/9781003024002-10